On Evolution of Some Associated Type Ruled Surfaces - Kelleci, Alev; Eren, Kemal (Murat TOSUN, 2020)
In this study, we define three new type ruled surfaces obtained by using the evolution of involute-evolute curve pair in Euclidean 3-space. Then, we give some nice results for the Gaussian curvature and the mean curvature of these surfaces. Moreover, considering the given involute-evolute curve pair, the graphics of these new type surfaces were drawn with the help of Mathematica. © MSAEN.
Keywords: evolution of space curve; inextensible surface; involute-evolute curve pair; Moving surface; Ruled surface